Pruning trial for Acacia mangium willd. plantation in Peninsular Malaysia - Nik Muhamad, Majid; Paudyal, Bimal K. (Elsevier, 1992)
A preliminary pruning trial for Acacia mangium was conducted at three different sites, Rantau Panjang, Setul and Kemasul Forest Reserves in the states of Selangor, Negeri Sembilan and Pahang, Peninsular Malaysia, respectively. Different pruning treatments ranging from pruning up to 2.5 to 6 m were assigned to various aged stands in these sites. All pruning treatments resulted in reduction in diameter growth. However, significant reduction in diameter growth was observed when crown removal was more than 40%. Taper study was done by taking diameter measurements at 0.15 m, at diameter breast height (1.37 m), at 2 and 4 m, respectively. The results indicated that pruning treatments have a significant effect on tapering of the stem. In general, there was a diameter decrease of 1 cm on every 1 m in height.